Obliteration of a glycinergic projection to the medial geniculate in an animal model of autism - Mansour, Yusra; Kulesza, Randy (Frontiers in Cellular Neuroscience, 2024)
Auditory dysfunction affects the vast majority of people with autism spectrum disorder (ASD) and can range from deafness to hypersensitivity. In utero exposure to the antiepileptic valproic acid (VPA) is associated with significant risk of an ASD diagnosis in humans and timed in utero exposure to VPA is utilized as an animal model of ASD. VPA-exposed rats have significantly fewer neurons in their auditory brainstem, thalamus and cortex, reduced ascending projections to the midbrain and thalamus and reduced descending projections from the cortex to the auditory midbrain. Consistent with these anatomical changes, VPA-exposed animals also have abnormal auditory brainstem responses. We have recently described a significant ascending projection from calbindin-positive neurons in the medial nucleus of the trapezoid body (MNTB) to the ventral division of the medial geniculate (vMG) in rats that bypasses the central nucleus of the inferior colliculus (CNIC). Since we found that axonal projections to the vMG in VPA-exposed rats are reduced beyond what is predicted from neuron loss alone, we hypothesize that VPA exposure would result in a significant reduction in the MNTB projection to the vMG. We examined this hypothesis by quantifying the proportion of retrogradely-labelled neurons in the MNTB of control and VPA-exposed animals after injections of retrograde tracers in the CNIC and vMG in control and VPA-exposed animals. Our results indicate that in control animals, the MNTB forms the largest projection from the superior olivary complex to the MG and that this projection is nearly abolished by in utero VPA exposure.